Correction: Supported two- and three-dimensional vanadium oxide species on the surface of β-SiC. Issue 18 (24th August 2017) - Carrero, Carlos A.; Burt, Samuel P.; Huang, Fangying; Venegas, Juan M.; Love, Alyssa M.; Mueller, Philipp; Zhu, Hao; Grant, Joseph T.; Mathison, Ricardo; Hanrahan, Michael P.; Rossini, Aaron; Ball, Madelyn; et al.
Abstract : Correction for 'Supported two- and three-dimensional vanadium oxide species on the surface of β-SiC' by Carlos A. Carrero et al., Catal. Sci. Technol., 2017, DOI: 10.1039/c7cy01036b.